Incidental Extracardiac Findings and Their Characterization on Cardiac MRI. (3rd October 2017) - Gravina, Matteo; Stoppino, Luca Pio; Casavecchia, Grazia; Moffa, Angelo Pio; Vinci, Roberta; Brunetti, Natale Daniele; Di Biase, Matteo; Macarini, Luca
Abstract : Background . Cardiac magnetic resonance imaging (cMRI) has recently emerged as a new noninvasive imaging modality that offers superior structural and functional assessment of the heart. cMRI benefits from a large field of view but, consequently, may capture incidental extracardiac findings (IEFs). We aimed to evaluate the frequency and significance of IEFs reported from clinically indicated cMRI scans. Methods . 742 consecutive patients (402 males and 340 females) referred to the Cardiac Magnetic Resonance Center of our University Hospital between January 2015 and December 2016 for clinically indicated cMRI were retrospectively enrolled for the evaluation of IEF prevalence and relevance. The median age of the subjects was 51 years (range: 5–85 years). Results . A significant number of patients who underwent cMRI had incidental and clinically significant IEFs (2% of the population, 11.4% of cases). cMRI allowed a correct diagnosis in 116/131 cases with a diagnostic accuracy value of 88.5%. Conclusions . IEFs on cMRI are not uncommon and lesions with mild or no clinical significance represent the most frequent findings. cMRI can characterize incidental findings with high accuracy in most cases.